K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 11 2020

M = x9 - x7 + x6 - x5 - x4 + x3 - x2 + 1

= ( x9 - x7 ) + ( x6 - x4 ) - ( x5 - x3 ) - ( x2 - 1 )

= x7( x2 - 1 ) + x4( x2 - 1 ) - x3( x2 - 1 ) - ( x2 - 1 )

= ( x2 - 1 )( x7 + x4 - x3 - 1 )

= ( x - 1 )( x + 1 )[ x4( x3 + 1 ) - ( x3 + 1 ) ]

= ( x - 1 )( x + 1 )( x3 + 1 )( x4 - 1 )

= ( x - 1 )( x + 1 )( x + 1 )( x2 - x + 1 )( x2 - 1 )( x2 + 1 )

= ( x + 1 )2( x - 1 )( x2 - x + 1 )( x - 1 )( x + 1 )( x2 + 1 )

= ( x + 1 )3( x - 1 )2( x2 + 1 )( x2 - x + 1 )

23 tháng 11 2017

x^4+x^2+1 = (x^4+2x^2+1)-x^2 = (x^2+1)^2-x^2 = (x^2-x+1).(x^2+x+1)

k mk nha

23 tháng 11 2017

bạn ơi bạn chưa bớt 2x^2 kìa

23 tháng 11 2017

x5-x4-1=x5-x3-x2-x4+x2+x+x3-x-1

=x2.(x3-x-1)-x.(x3-x-1)+(x3-x-1)

=(x3-x-1)(x2-x+1)

23 tháng 11 2017

x^4+x^2+1 = (x^4+2x^2+1)-x^2 = (x^2+1)^2-x^2 = (x^2-x+1).(x^2+x+1)

k mk nha

10 tháng 10 2021

\(x^2\left(4-x\right)+9\left(4-x\right)=\left(x^2+9\right)\left(4-x\right)\)

3 tháng 10 2019

a) \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)-15\)

\(=\left(x+1\right)\left(x+4\right)\left(x+2\right)\left(x+3\right)-15\)

\(=\left(x^2+5x+4\right)\left(x^2+5x+6\right)-15\)(1)

Đặt \(x^2+5x+4=t\)

\(\Rightarrow\left(1\right)=t\left(t+2\right)-15=t^2+2t+1-16\)

\(=\left(t+1\right)^2-4^2=\left(t+5\right)\left(t-3\right)\)

\(=\left(x^2+5x+9\right)\left(x^2+5x+1\right)\)

3 tháng 10 2019

b) \(\left(2x+5\right)^2-\left(x-9\right)^2\)

\(=\left(2x+5+x-9\right)\left(2x+5-x+9\right)\)

\(=\left(3x-4\right)\left(x+14\right)\)

22 tháng 7 2017

x9+x3+x2+x1

= (x9-x6)+(x6-x3)+x2+x+1

= x6(x3-1)+x3(x3-1)+x2+x+1

= x6(x-1)(x2+x+1)+x3(x-1)(x2+x+1)+(x2+x+1)

= (x2+x+1)(x7-x6+x4-x3+1)